Integrated Management System: The Converging of Key Quality Standards into Single Standard - Muzaimi, H.; Hamid, S.R.; Isa, S.; Chew, B.C. (International Journal of Human and Technology Interaction (IJHaTI), 2019)
This paper discussed the Integrated Management System (IMS) that combined the quality (ISO 9001), environment (ISO 14001) and occupational health and safety (OHSAS 18001) management system. In order to investigate the component that can be integrated with IMS, the research focuses on identifying two parts, 1) Converged component and 2) Diverged component. A series of the interview was conducted through in-depth interviews with 5 experts in this field, while data collected were analyzed qualitatively. As a conclusion, this research identified the component in IMS that can be applied for better quality management in terms of cost, time and resources towards sustainability practices in the organization.